Increasing informativity of digital radiographic systems - Opolonin, O.D.; Ryzhikov, V.D. (Functional Materials, 2013)
In this paper questions of improving the information content of radiographic images is considered. Source of the new information is X-ray images of inspected object registered in several energy ranges. Three energy X-ray images of test objects with an effective atomic number from 7.08 to 8.07 were obtained. Using a photodiode-scintillator type detectors based on scintillator ZnSe(Te) the accuracy of substances separation by the effective atomic number ∼5 % was achieved. We proposed a method for reconstructing the energy dependence of the mass attenuation coefficient.